Driving Social Entrepreneurship Performance Through Entrepreneurial Orientation in Agriculture and Food Sectors in Yogyakarta - Suprihanti, Antik; Soriano, Jerome Duque; Kuncoro, Andreas Mahendra; Cahyanto, Ichsan Nur; Nusantari, Jasmine Rahma; Alfreda, Sabrina Marsha (School of Business, IPB University (SB-IPB), 2025)
Background: Background: Social enterprises in developing countries often faced internal and external challenges in achieving sustainable impact, especially in agriculture and food sectors. Entrepreneurial Orientation (EO), consisting of innovativeness, proactiveness, risk-taking, autonomy, and competitive aggressiveness, has emerged as a potential driver of Social Entrepreneurship Performance (SEP). However, its nuanced effects in mission-driven contexts remain underexplored.Purpose: This study aims to investigate the influence of Entrepreneurial Orientation (EO) on Social Entrepreneurship Performance (SEP) among small and medium enterprises (SMEs) in the agricultural and food sectors in Yogyakarta, Indonesia, by analyzing the distinct contributions of each EO dimension.Design/Methodology/Approach: A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from 32 purposively selected SMEs. EO was modeled as a higher-order construct composed of five lower-order dimensions, and SEP was measured based on social engagement and partnership benefits.Conclusion: The findings confirm that EO significantly and positively influences SEP. Innovation and proactiveness were the strongest contributors to EO, while risk-taking negatively affected autonomy, and competitive aggressiveness showed moderate impacts. The study highlights the need for strategic emphasis on innovation and proactiveness, with cautious risk management and aligned autonomy to enhance social enterprise outcomes.Originality/Value: This research contributes to the limited empirical evidence on EO's role in social enterprise performance within agriculture-based SMEs in developing countries. It offers nuanced insights into how EO dimensions function differently in resource-constrained, socially driven settings. It also provides actionable implications for social enterprise managers seeking to enhance organizational sustainability and social impact. These findings guide social enterprise managers to balance innovation and proactiveness while managing risk conservatively to enhance sustainable impact. Keywords: entrepreneurial orientation, social entrepreneurship performance, agriculture and food industries